The factor analysis of demographic, purchasing behaviour, and customer satisfaction of budget hotel - Simangunsong, Eliot (BISMA (Bisnis dan Manajemen), 2021)
Budget hotels are growing in Indonesia because of the increased number of business travelers and budget travelers. Nevertheless, budget hotels face increasingly fierce competition to attract customers and sustain growth. This research aims to identify factors that determine budget hotels’ guest satisfaction. A quantitative approach with the survey as a research instrument has been applied and collected 363 respondents. Data analysis using SPSS shows that monthly spending, frequency of staying, and lifestyle factors are the main determinants of visitor’s decision to stay in a budget hotel. This result indicates that the more prudent the visitor lifestyle, the more likely they will remain at a budget hotel. Furthermore, the Friedman test shows the degree of importance of each factor influencing guest satisfaction in a budget hotel. A posthoc analysis with Wilcoxon signed-rank tests (Bonferroni correction applied) found that cleanliness, price, and location become the utmost important factors determining guest satisfaction.